Makna Tradisi Balimau Kasai di Desa Tanjung Berulak Kecamatan Kampar - Asriwandari , Hesti; Susanti, Rina; Hidayat, Rian (Universitas Muhammadiyah Malang, 2023)
Kebudayaan selalui melekat pada suatu daerah kebudayan yang dilakukan secara turun temurun kemudian menjadi tradisi dan ciri khas suatu daerah. Tradisi balimau bakasai sebagai upacara penyambutan bulan suci ramadhan yang dilaksanakan 1 hari sebelum bulan suci ramadan dengan cara mandi bersama di sungai Kampar yang bertujuan untuk menyucikan diri dan bersilaturahmi saling memaafkan dalam menyambut bulan ramadhan. Seiring berjalannya waktu tradisi ini kian menipis dan habis keasliannya hal itu dikarenakan tujuan awal balimau kasai berubah dengan ajang mencari jodoh bagi anak muda , mabuk-mabukan dan perbuatan tercela lainnya. penelitian ini bertujuan untuk mengetahui tata laksana balimau kasai dan makna sosial, budaya dan ekonomi bagi masyarakat desa Tanjung Berulak. Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Pengumpulan data yang dilakukan menggunakan teknik wawancara mendalam dan dokumentasi. Hasil penelitian menjelaskan bahwa tata laksana tradisi balimau bakasai dimulai dari berziara h kubur, tablig akbar dan santunan anak yatim piatu. Adapun makna yang terkandung dalam tradisi balimau bakasai antara lain dijelaskan makna sosial balimau bakasai adalah sebagai suatu interaksi sosial antara masyarakat di Desa Tanjung Berulak dengan adanya silaturahmi dan gotong royong, selain itu juga terdapat makna budaya yang menyebutkan bahwa balimau kasai adalah budaya masyarakat di daerah tersebut dan rutin dilaksanakan setiap tahun dalam menyambut bulan suci Ramadhan yang dipercaya masyarakat untuk pembersihan diri dari hadas kotor yang melekat dan adanya permainan-permainan rakyat seperti panjat batang pinang dan pacu goni. Terakhir dengan banyaknya antusias masyarakat untuk mengikuti tradisi balimau kasai juga membawa berkah untuk masyarakat yang berjualan di tempat. Culture is always attached to a cultural area which is passed down from generation to generation and then becomes a tradition and characteristic of an area. The Balimau Bakasai tradition is a ceremony to welcome the holy month of Ramadan which is held 1 day before the holy month of Ramadan by bathing together in the Kampar river which aims to purify oneself and stay in touch to forgive each other in welcoming the month of Ramadan. As time goes by, this tradition becomes thinner and loses its authenticity, this is because the original purpose of balimau kasai has changed to finding a mate for young people, drinking and other despicable acts. This research aims to determine the management of balimau kasai and its social, cultural and economic meaning for the people of Tanjung Berulak village. This research uses descriptive qualitative research methods. Data collection was carried out using in-depth interview techniques and documentation. . The results of the research explain that the implementation of the balimau bakasai tradition begins with visiting graves, tablig akbar and providing compensation for orphans, then ends with bathing with balimau kasai in the Kampar river, bringing kasai, kaffir lime, lime and pandan as well as various potpourri flowers which are used as body fragrance with the aim of cleansing oneself from dirty hadas and as a form of mutual forgiveness before the month of Ramadan. The meaning contained in the balimau bakasai tradition, among others, explains the social meaning of balimau bakasai as a social interaction between the people in Tanjung Berulak village with friendship and mutual cooperation, apart from that there is also a cultural meaning which states that balimau kasai is the culture of the people in the area and is routinely carried out every year to welcome the holy month of Ramadan which is believed by the community to cleanse themselves of the dirty hadas that sticks to them. Besides that, there are also folk games such as climbing areca nut sticks and spurting jute. Lastly, the enthusiasm of many people to follow the Balimau Kasai tradition also brings blessings to the people who sell at that place with an increase in income of 400-1000,000 when the tradition lasts.